Labor Dystocia. Issue 6 (November 2020) - Simpson, Kathleen Rice
Abstract : The Agency for Healthcare Research and Quality commissioned a systematic review of the evidence on labor dystocia that had been published from January 1, 2005 to February 15, 2019, with a goal of identifying effective treatment measures for healthy women in spontaneous labor without pregnancy complications. A summary of the findings is presented.